Hypertension after Kidney Transplantation: Clinical Significance and Therapeutical Aspects - Severova-Andreevska, Galina (Open Access Maced J Med Sci, 2019)
Most of the kidney transplanted patients develop arterial hypertension after renal transplantation. Together with very well-known and usual risk factors, post-transplant hypertension contributes to the whole cardiovascular morbidity and mortality in the kidney transplant population. The reasons of post-transplant hypertension are factors related to donors and recipients, immunosuppressive therapy like Calcineurin Inhibitors (CNI) and surgery procedures (stenosis and kinking of the renal artery and ureteral obstruction). According to Eighth National Committee (JNC 8) recommendations, blood pressure > 140/90 mmHg is considered as hypertension. The usual antihypertensive drugs used for the control of hypertension are Calcium channel blockers (CCB), Angiotensin-converting enzyme (ACE) inhibitors, Angiotensin –II receptor blockers (ARB), B- blockers and diuretics. Follow the KDIGO guidelines the target blood pressure < 140/90 mmHg for patients without proteinuria and < 125/75 mmHg in patients with proteinuria is recommended. Better control of post-transplant hypertension improves the long-term graft and patient’s survival.